19‐6: Invited Paper: A Novel Process for Fabricating High‐Resolution and Very Small Pixel‐pitch GaN LED Microdisplays. Issue 1 (2nd June 2017) - Templier, François; Benaïssa, Lamine; Aventurier, Bernard; Nardo, Christine Di; Charles, Matthew; Daami, Anis; Henry, Franck; Dupré, Ludovic
Abstract : A new approach for fabricating very‐small pixel pitch GaN microdisplays is proposed. MicroLEDS obtained from silicon grown epi GaN layers exhibit performances comparable to those obtained on classical sapphire templates. This technology shows very great promises in the fabrication of high brightness, ultra‐high‐resolution microdisplays required for augmented reality systems.